Geometric Fuzzy Techniques for Guidance of Visually Impaired People - Adán Landa-Hernández; Heriberto Casarubias-Vargas; Eduardo Bayro-Corrochano (Applied Bionics and Biomechanics)
In this paper we present the design of a device to guide the visually impaired person who normally uses a cane. We propose a non-invasive device that will help blind and visually impaired people to navigate. The system uses stereoscopic vision, a RGB-D sensor and an IMU to process images and to compute the distances from obstacles relative to cameras and to search for free walking paths in the scene. This computing is done using stereo vision, vanishing points, and fuzzy rules. Vanishing points are used to obtain a main orientation in structured spaces. Since the guidance system is related to a spatial reference system, the vanishing point is used like a virtual compass that helps the blind to orient him- or herself towards a goal. Reinforced with fuzzy decision rules, the system supports the blind in avoiding obstacles, thus the blind person is able to cross structured spaces and avoid obstacles without the need for a cane.